The relationship between learner autonomy and English language proficiency of non-TESL teacher trainees / Fauziah Ismail - Ismail, Fauziah (2013)
Learner autonomy refers to learner 's ability to take responsibility for their ownlearning. Previous studies revealed that students' English language proficiency could be influenced by learner autonomy. The purpose of this mixed-method study is to investigate the relationship between learner autonomy and English proficiency of a selected group of teacher trainees. The sample comprises 90 Non-TESL teacher trainees from four Institutes of Teacher Education (IPG) in Klang Valley. The main instrument used was a questionnaire which was adapted from Guglielmino (1977). However, to cross-validate the findings, structured interviews were conducted. Descriptive statistics was used to determine the teacher trainees' level of learner autonomy and English Language proficiency, consisted of percentages, mean scores and Standard Deviations. The Spearman Correlation Coefficient was used to study the relationship between the learner autonomy and English Language proficiency. The study reveals that the Non-TESL teacher trainees' learner autonomy is average and their level of English proficiency was not excellent. The analysis from Spearman's Rho Correlation Coefficient test revealed that the learners' English proficiency was not significantly related to their learner autonomy (r -0.016). The findings imply that the learner autonomy is independent in affecting the students' English proficiency. Furthermore, equal emphases on content or "what to learn' and process or 'how to learn' appear to be the key factors that need to be considered when planning or designing English Language course programme. Such a move would help equip learners with the necessary knowledge and skills to achieve learner autonomy for life-long learning. IV